Villains or scapegoats? The role of subprime borrowers in driving the U.S. housing boom - James Conklin; W. Scott Frame; Kristopher Gerardi; Haoyang Liu (Federal Reserve Bank of Atlanta, 2018)
An expansion in mortgage credit to subprime borrowers is widely believed to have been a principal driver of the 2002-06 U.S. house price boom. Contrary to this belief, we show that the house price and subprime booms occurred in different places. Counties with the largest home price appreciation between 2002 and 2006 had the largest declines in the share of purchase mortgages to subprime borrowers. We also document that the expansion in speculative mortgage products and underwriting fraud was not concentrated among subprime borrowers.
Keywords: D14; D18; D53; G21; G38; 330; mortgages; subprime; house prices; credit scores; housing boom